DAYA SAING EKSPOR KOMODITAS TEMBAKAU INDONESIA SELAMA PANDEMI COVID-19 - Riska Lujeng Fitrianti; Ahmad Zainuddin; Saktyanu Kristyantoadi Dermoredjo (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2024)
The excise contribution from the Tobacco Products Industry (IHT) in 2020 amounted to Rp170.24 trillion or 96.56% of all Indonesian excise revenue. The Covid-19 pandemic caused tobacco exports in 2020 to decrease by 6.41% or 2,134 tons. Based on these conditions, it is necessary to research the competitiveness of tobacco exports during the Covid-19 pandemic in the main destination countries. The method of determining the location used is a purposive method, namely in Belgium, Singapore, Dominican Republic, Sri Lanka, Germany, the Netherlands, and the United States. The data used is time series data for 38 months starting from August 2018 to September 2021. The analysis methods used are IIT (Intra Industry Trade), RCA (Revealed Comparative Advantage), and EPD (Export Product Dynamic). The results showed a) IIT analysis, that most countries experienced a decline during the Covid-19 pandemic. Countries that experienced a decrease were the Netherlands, Dominican Republic, Singapore, and Sri Lanka, while those that experienced an increase were Belgium, Germany, and the United States. b) RCA analysis in the seven main destination countries showed a strong position. c) EPD analysis of most of the main destination countries for tobacco exports showed positive results, except for the United States which experienced a decrease.